Analysis of Smoking Habits, Sleep Quality, and Eating Patterns with The Incidence of Hypertension in The Work Area of The Teruwai Community Health Center, Pujut District, Central Lombok Regency in The Period of 20-31 August 2024 - Adipati, Adyen Widya; Pramana, Kadek Dwi; Ardianti, Nurul Endah; Dharmapala, Juslaksmi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Systolic and diastolic blood pressure readings of 140 mmHg and 90 mmHg, respectively, are indicative of hypertension, a condition that can lead to major consequences like heart attacks, strokes, and early death. The prevalence of hypertension increased significantly in 2018, reaching 1.3 billion individuals worldwide. This study aims to determine the relationship between smoking habits, sleep quality, and dietary patterns with the incidence of hypertension in the Working Area of Teruwai Community Health Center, Pujut Subdistrict, Central Lombok Regency, during the period of August 20–31, 2024. The study utilized a cross-sectional design with a sample size of 108 respondents, selected through simple random sampling. The statistical test employed was the chi-square test. The results found 76 respondents (70.4%) had high blood pressure. Hypertensive behavior and smoking significantly correlated (p-value = 0,000). Likewise, there is a significant relationship between food patterns and hypertension (p-value = 0,000) and sleep quality and hypertension (p-value = 0,000). The conclusion is that risk factors for hypertension include smoking habits, sleep quality, and dietary patterns, all of which significantly influence the incidence of hypertension.